Lexical Choices as Affective Stance: Fans’ Responses to Eaj’s Activism on Twitter - Sitti Kamila Meutia Sani (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines how fans of the singer and celebrity Eaj (known as Jars) express affective stance through their lexical choices in responses to his humanitarian activism on X (formerly Twitter). When Eaj publicly voiced support for Palestine and Sudan, fans engaged actively through replies and quote tweets, displaying emotional alignment, shared values, and moral support. Using a qualitative discourse analysis approach, the study combines Hyland’s (2005) stance model with Du Bois’s (2007) stance triangle to identify attitude markers, evaluative language, and relational positioning. Thirty-three fan responses were selected from two threads related to activism, focusing on expressions of admiration, gratitude, empathy, and solidarity. The analysis reveals that fans not only evaluate the issues raised by Eaj but also position themselves as supportive, morally engaged participants, aligning with both Eaj and other users in the discourse. These affective expressions reveal how digital fandom can construct collective emotional meaning and reinforce parasocial bonds in activism contexts. While limited in scope, the study highlights the usefulness of combining interpersonal stance theory with relational stance analysis to understand the emotional meaning-making process in online fandom. The findings contribute to growing discussions on digital fandom discourse, demonstrating how linguistic choices serve as tools for expressing attachment, advocacy, and shared humanitarian concern.